INTER TWIN MEMBRANE IN SONOGRAPHIC EVALUATION OF TWIN GESTATIONS - Nayab Alia; Amber Bukhari (Journal of University Medical & Dental College, 1970)
ABSTRACT Objective: To assess the value of ultrasound measurement of twin dividing membrane thickness in predicting chorionicity. Study design: Observational study. Sampling technique: All patients with twin gestation presented at Radiology Department, Madina Teaching Hospital from Jan 2010 to December 2011. Material and methods: This was a prospective study of 60 twin pregnancies between 16-35 weeks gestation. Sonographic examination for presence or absence of membrane was done. If membrane is visualized, the thickness of membrane was measured using technique with measurements are taken only when membranes are parallel to ultrasound beam. The thickness of 2mm is taken as cutoff point for chorionicity. Twin gestation was classified dichorionic if either confirmed by histological examination of placenta or by clinical findings (the male and female gender of neonates or presence of two separate placentas at delivery). Results: Out of 60 twin pregnancies in which amnionicity and chorionicity could be determined, 45(75%) were dichorionic diamniotic, 14 (23%) were monochorionic diamniotic and 1(2%) was monochorionic monoamniotic. In 42 of these (45) a thick separating membrane was identified at least on one sonogram (93 sensitivity). Twenty scan were obtained on monochorionic pregnancies. Thin membrane was identified in 13 (65%) of these. In two patients (10%) the visualized membrane could not be categorized as thin/thick. No membrane can be identified in five (25%) patients. Conclusion: Membrane characteristic should be used in conjunction with other sonographic criteria such as number of placental sites and fetal gender to predict the chorionicity of twin pregnancy.